Sistem Pendeteksi Wajah Berjerawat Pada Citra Digital Menggunakan Metode Viola Jones - Windy Maulianda; Achmad Fauzi; Mili Alfhi Syari (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
The development of computer technology that is increasingly advanced and sophisticated, makes computer experts have the desire to create the latest software in computers. One of them is image data processing by utilizing digital image data processing that can be used in recognizing the shape of an object. Acne (acne vulgaris) is a disease caused by chronic inflammation of the pilosebaceous unit characterized by the formation of comedones, papules, pustules, nodules that can grow on the face, back, chest, arms, legs. Acne itself arises due to hormonal changes experienced by sufferers. To find out the acne can be seen directly or palpated on the face area. Improper handling of acne can harm facial skin and cause inflammation. It takes a system that can identify acne by applying image processing. The Viola Jones method is an object detection method that has a fairly high level of accuracy, which is about 93.7%